The performance evaluation of corporate universities. Issue 3 (3rd July 2017) - Cappiello, Giuseppe; Pedrini, Giulio
Abstract : The aim of this paper is to illustrate the phenomenon of corporate universities from the perspective of the evaluation of their performance. Corporate universities have a hybrid nature that can be referred to both as a business unit and as a higher education institution. Having reviewed the literature on corporate universities and performance evaluation of these kind of entities, we present the results of a survey on Italian corporate universities. Results shows that an appropriate framework for the evaluation of corporate university performance need to distinguish among the different types of corporate universities that are actually in place according to their mission and degree of openness to the external environment.